Analisis Manajemen Strategi PT. Astra Agro Lestari Tbk dengan Pendekatan SWOT, SPACE, BCG, IE Matrix, dan Grand Strategy Matrix - Ivan Aubrey Adianto (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
This study aims to analyze the strategic management of PT Astra Agro Lestari Tbk in addressing the increasingly competitive and sustainability-oriented palm oil industry. The analysis employs the SWOT, SPACE, BCG, IE, and QSPM approaches to identify the company’s strategic position and formulate appropriate alternative strategies. The analysis indicates that the company possesses strong internal capabilities and potential to support sustainable growth strategies. The application of these analytical frameworks is expected to enhance the company’s competitiveness, improve operational efficiency, and strengthen its commitment to environmental and social sustainability principles. This study contributes to a deeper understanding of strategic management implementation within the agribusiness sector, particularly in Indonesia’s palm oil industry. Kata kunci: management strategy, SWOT, SPACE, BCG, IE, QSPM, palm oil